Kajian Produktivitas Pekerja Sektoral dan Regional di Propinsi Sulawesi Tenggara - Harafah, L. M. (Universitas Brawijaya, Indonesia, 2008)
The aim of this research was to analysis/lecture in detail about labour productivity sectoral and regional in South-East Sulawesi Province. The research limited at situation output (PDRB) and labour, sectoral or regional. The analysis method used in this research were quantitative and qualitative descriptive. Quantitative method, formulation that used were Productivity Index and Productivity Variable Index of labour; sectoral or regional. The results of research showed that the labour productivity index in five years (2003-2007), average to increasing, sectoral or regional. According the result of research indicated that Productivity: Variable Index of sectoral labour in 2007 indicated that increasing of significance for regional sector, Productivity Variable Index of labour olso increasing